An act for the appointment of commissioners of wrecks, and in relation to their duties and the duties of others, in relation to wrecks and wrecked property (House doc. (North Carolina. General Assembly. House of Commons), 1846)
1846 bill for the Appointment of Commissioners of Wrecks, which dealt with their duties and those of others regarding wrecks and wrecked property. This bill allowed the owners or duly authorized agent to have primary responsibility for the disposition of stranded or wrecked property, when they are present to do so.